2008
DOI: 10.1002/ptr.2604
|View full text |Cite
|
Sign up to set email alerts
|

Mint oil (Mentha spicata Linn.) offers behavioral radioprotection: a radiation‐induced conditioned taste aversion study

Abstract: Mentha spicata Linn. (mint), a herb well known for its gastroprotective properties in the traditional system of medicine has been shown to protect against radiation-induced lethality, and recently its constituents have been found to possess calcium channel antagonizing properties. The present study examined the behavioral radioprotective efficacy of mint oil (obtained from Mentha spicata), particularly in mitigating radiation-induced conditioned taste aversion (CTA), which has been proposed as a behavioral end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Mint oil blocked the saccharin avoidance response within 5 post-treatment observational days and demonstrated that mint oil may be of use in preventing the radiation-induced behavioral changes. [28] …”
Section: Mint Mitigates Radiation-induced Behavioral Perturbations Inmentioning
confidence: 97%
See 1 more Smart Citation
“…Mint oil blocked the saccharin avoidance response within 5 post-treatment observational days and demonstrated that mint oil may be of use in preventing the radiation-induced behavioral changes. [28] …”
Section: Mint Mitigates Radiation-induced Behavioral Perturbations Inmentioning
confidence: 97%
“…Due to these reasons the conditioned taste aversion has been proposed as a standard procedure and a reliable paradigm for evaluating behavioral alterations induced by radiation or other environmental agents/toxins. [27] Haksar et al, [28] have observed that the oil from M. spicata mitigated the radiation-induced conditioned taste aversion in rats. Intraperitoneal administration of the oil before exposure to radiation offered significant radioprotection against conditioned taste aversion.…”
Section: Mint Mitigates Radiation-induced Behavioral Perturbations Inmentioning
confidence: 98%
“…was effective in mitigating radiation-induced conditioned taste aversion (CTA), a phenomenon understood to be controlled in rodents by the same pathways that control nausea and vomiting in humans. 45 It was observed that the intraperitoneal administration of mint oil (5, 7.5, 10, 12.5, and 15% v/v) 1 hour before exposure to 2 Gy of whole body irradiation showed significant decrease in CTA at all doses, when compared with the 2 Gy radiation control at all time points (1, 2, 3, 4, and 5 days post irradiation). However, the best effect was observed as follows 10% > 12.5% > 15% > 7.5% > 5%.…”
Section: Mint Oil In the Prevention Of Rinvmentioning
confidence: 91%
“…However, the best effect was observed as follows 10% > 12.5% > 15% > 7.5% > 5%. 45 Mechanistically, it is quite possible that the free radical scavenging and the antioxidant effects of mint may have contributed to the reduction in CTA. Studies have also shown that rotundifolone, an active constituent of mint oil, mimics the effects produced by calcium channel blockers, and thus can neutralize the injurious effects of biogenic amines such as histamines and 5-HT and also modulate vagal activity and reduce intestinal motility and contractility.…”
Section: Mint Oil In the Prevention Of Rinvmentioning
confidence: 99%
“…This herb is widely used in treatment of fever, vomiting, sinusitis and common cold (Güney et al, 2006). The anti-microbial, radioprotective, anti-oxidant, anti-tumoral and anti-inflammatory effects of spearmint have been reported (Lixandru et al, 2010;Haksar et al, 2009;Pearson et al, 2010;Hussain et al, 2010;Arumugam and Ramesh, 2009). Besides, the toxic effect of Mentha pulegium (another specious of Mentha genus) on some cancer cells has been shown (Shirazi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%